MiRNAs and long noncoding RNAs as biomarkers in human diseases. (March 2013) - Van Roosbroeck, Katrien; Pollet, Jeroen; Calin, George A
Noncoding RNAs (ncRNAs) are transcripts that have no apparent protein-coding capacity; however, many ncRNAs have been found to play a major biological role in human physiology. Their deregulation is implicated in many human diseases, but their exact roles are only beginning to be elucidated. Nevertheless, ncRNAs are extensively studied as a novel source of biomarkers, and the fact that they can be detected in body fluids makes them extremely suitable for this purpose. The authors mainly focus on ncRNAs as biomarkers in cancer, but also touch on other human diseases such as cardiovascular diseases, autoimmune diseases, neurological disorders and infectious diseases. The authors discuss the established methods and provide a selection of emerging new techniques that can be used to detect and quantify ncRNAs. Finally, the authors discuss ncRNAs as a new strategy for therapeutic interventions.